Eight Pieces for Four Timpani: one player - CARTER, Elliott (Associated Music Publ., 1968)
Buku ini terdiri dari I. Saeta, II. Moto Perpetuo, III. Adagio, IV. Recitative, V. Improvisation, VI. Canto, VII. Canaries, VIII. March